An application of the knowledge management maturity model: the case of credit unions. Issue 3 (1st August 2016) - Serenko, Alexander; Bontis, Nick; Hull, Emily
Abstract: The purpose of this study is to investigate the level of knowledge management (KM) maturity of credit unions. The application of a maturity model to 15 credit unions in North America revealed that an overall level of KM maturity is at an early stage of development, but there are signs of future improvement. Credit unions operate in a highly competitive, knowledge-intensive financial industry and experience various pressures to increase their efficiency, which they can achieve through the implementation of KM solutions. Despite the absence of official KM strategies, KM projects were introduced locally in order to fill particular knowledge gaps. The availability of IT infrastructure and the implementation of KM-related technologies alone are insufficient to ensure universal success of organizational KM activities. Credit union managers periodically access and use academic research in their decision making. At the same time, they prefer accessing scholarly knowledge in translated form from books, practitioner magazines, and consultants. It was concluded that organizations competing in the knowledge-intensive sector have an inner need for KM solutions.